A Rover's Story - Warga, Jasmine; Rockefeller, Matt (New York, NY : Balzer + Bray, an imprint of HarperCollinsPublishers, 2022)
Built to explore Mars, Resilience begins to develop human-like feelings as he learns from the NASA scientists who assembled him, and as he blasts off and explores Mars, Resilience must overcome different obstacles as he explores the red planet.
Includes bibliographical references.
Keywords: Roving vehicles (Astronautics) -- Juvenile fiction; Emotions -- Juvenile fiction; Roving vehicles (Astronautics) -- Fiction; Emotions -- Fiction; Mars (Planet) -- Juvenile fiction. -- Exploration; Mars (Planet) -- Fiction. -- Exploration; Novels